Readers and collaborators: Female Voices in the Afro-Porteño Press in Buenos Aires at the End of the 19th century - Moreno-Chuquen, Liz (Comunicación y Medios, 2021)
This study examines the role of Afroporteño women in two Afroporteño newspapers, namely La Perla (Buenos Aires, 1878-1879) and El Unionista (Buenos Aires, 1877-1878). By examining the beats devoted to news about the community’s social activities, the publication of letters from readers, and the songs of carnival societies, this article analyzes the construction of an Afro-feminine discourse under a decolonial feminist perspective. The analysis indicates that women supported these journalistic projects as readers and contributors. Women’s contributions to the press problematize the editorial frame under which the role of women was limited to the domestic-private space. These publications by women build up a more plural Afro-feminine discourse, although it is not entirely autonomous from the frameworks of domination and marginalization Afroporteño women had to coexist with.